Assessment of Control Measures and Trends of Malaria in Burie-Zuria District, West Gojjam Zone, Amhara Region, North West Ethiopia. (11th June 2015) - Kassa, Addisu Workineh; Tamiru, Mulugojjam Andualem; Yeshanew, Addisu Gize
Abstract : Introduction . Malaria is caused by the protozoan parasite Plasmodium and transmitted by the bite of Anopheles mosquitoes. The aim of this study was to assess control measures and trends of malaria and guide intervention measures at Burie-Zuria district, Amhara region. Methods . Descriptive cross-sectional assessment of control measures was undertaken. We used health facility records of malaria data. We surveyed households for clinical malaria cases and utilization of Long Lasting Impregnated Nets (LLINs) and its status; the condition of Indore Residual Spraying (IRS) operation at household level was observed. Results . In Zelma-Shenbekuma kebele (village) the prevalence rate of confirmed malaria cases in the 2nd week of September was 1.2 per 1000 (17) of population and increased to 11.5 per 1000 (163) of population in the 3rd week of September 2012 and reached 16.6 per 1000 (236) of population in the 1st week of November 2012. The attack rate was the highest in 1-<5 years 120.3 per 1000 (1920) of population. LLINs were distributed four years back and only five of the fifteen respondents knew about the use of LLINs and used it regularly. Four of the fifteen households were not sprayed with IRS. Conclusion . Vector control interventions were not carried out timely.